PERBEDAAN MOTIF DAN KEPUASAN BERKOMUNIKASI PENGGUNA APLIKASI CHATTING LINE DAN BLACKBERRY MESSENGER (BBM) PADA MAHASISWA UNIVERSITAS RIAU - Muhammad Irfan; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to know the difference of motive and satisfaction to communicate user of Line and Blackberry Messenger (BBM) chat application on Student of Riau University. Population in this research is student of Riau university which use application of chatting Line and BBM which counted active in year 2017 that is 37001 students. However, it is not known exactly the number of application population Line and BBM on students of the of Riau University. Because the population is large and the number is not known exactly, then in determining the sample using the formula Unknown Populations who get the sample of 135 students. And for the selection of respondents conducted degan use Incidental Sampling sampling method. To answer the hypothesis then use the Independent Samples T Test with the help of SPSS 21 program. Based on comparison of mean GS application score line with mean score of GS application of fuel, it is obtained that mean application score of 4,047 is superior compared to mean score of application of BBM of 4.036 GS Line> GS Bbm comparison of mean score of GO application line with mean score GO of BBM application, obtained that the mean of the Line application score of 4,085 is superior to the mean score of the BBM application of 4,036 GO Line> GO Bbm. Then based on the value of t arithmetic and significance of motive variables and satisfaction of the use of BBM chat application and Line Motif. Obtained t value (0,230) <t table (1,969) or significance (0,818)> 0,05. This means that there is no difference in the motive of using BBM chat application with Line. Satisfaction. Obtained value t count (3.290)> t table (1,969) or significance (0.001) <0.05. This means that there is a difference in the satisfaction of using BBM chat application with Line.Keywords: Motives, Satisfaction, Line and Blackberry Messenger (BBM)